Design and Development of Information Systems for Entrepreneurs Database in Nakhon Pathom Rajabhat University - lalitwasuphinyo, sirikanya (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
The purposes of this research were 1) to design and develop an information system for entrepreneurs database in Nakhon Pathom Rajabhat University, 2) To evaluate the efficiency of the information system for entrepreneurs database in Nakhon Pathom Rajabhat University, And 3) to assess the validity of the information system for entrepreneurs in Nakhon Pathom Rajabhat University. satisfaction of users of the information system for the database of entrepreneurs within Nakhon Pathom Rajabhat University. This research study developed the system by using the System Development Life Cycle (SDLC) by building application software on MySQL database and using PHP language to develop the system. The tools used to evaluate the system are: 1) System Quality Assessment Form by experts and 2) a satisfaction assessment form after testing the system by users. After the development of the system is completed the researcher has tested the system and improved some parts to be suitable for use. and led to two experts in information technology selected by a specific method to assess the quality of the system. And bring it to users, including 3 supervisors, 1 Income and property officer, 24 entrepreneur representatives, A total of 28 people, To try out the system and assess the satisfaction of the system. After having tried the system, The research results found that Experts give their opinion that the system is of good quality. it is at the highest level (=4.78) and users are satisfied with the system. it is at the highest level (=4.73). it can be concluded that Information system for the database of entrepreneurs within Nakhon Pathom Rajabhat University that the researcher has developed can be used in work appropriately and the information system can respond to the intended use. and allows operators to work quickly and increase accuracy and can be verified